Benefits and Effectiveness of Automatic Farmer Pest Repellent - Krisna Dwi Nurikhsani; Jonah Mupita (ASEAN Journal of Science and Engineering, 2022)
Indonesia is one of the countries that is famous for its extensive agricultural land so it is not surprising that Indonesia is called an agrarian country. In addition, most of the population earns a living as farmers, but this does not make Indonesia the largest rice producer in the world. Apart from that, farmers in Indonesia have difficulty dealing with pests that make them suffer losses due to crop failure. This study aims to explain the benefits and effectiveness of an automatic tool that can repel farmer pests, especially rats and birds. In this tool there is a Passive Infrared Receiver sensor that functions to detect the presence of farmer pests, then the servo motor will activate the bell, and pull the bell to produce a sound that scares birds and mice. The mechanism is controlled by a microcontroller, namely Arduino ATmega 2560. This tool is an innovation from previous technologies so that farmers' problems regarding farmer pests can be solved easily.